(untitled) (Comillas Journal of International Relations, 2016)
For the first two centuries of Qatar’s modern history its leading Sheikhs secured security by allying with at least one more powerful political entity at a time, while maintaining a largely inoffensive and muted posture. But an emerging leadership in the 1980s had new ideas. Security was still predicated on one central protective relationship, but this dependency was diversified as Qatar embedded itself into energy, security, financial, and political dynamics, if not also the wider consciousness, of key states around the world. Additionally, the state cultivated a reputation as a relatively neutral actor so that, overall, Qatar was well positioned for the eventual departure of its central ally. Yet Qatar’s reputation as an uncontroversial, peaceable, quasi-neutral state was undermined as its leadership systematically chose sides during the Arab Spring. Without the capacity, resources, or experience to effectively involve itself in the Gordian conflicts that emerged from the Spring, Qatar gained a reputation as a dangerous dilatant, stoking anger among key allies in the Arab and western worlds. Its young Emir must now navigate a hazardous path, stuck between path dependency promoting the maintenance of old associations and the reality that Qatar struggles to control and use these relations effectively.